A Conversation About Generative Artificial Intelligence. - Alaoui, Siham; Chokly, Kit; Ciufo, Carly; Robichaud, Léon; Stark, Luke; Turkel, William J. (Canadian Historical Review, 2026)
This is a wide-ranging conversation on the ways that generative artificial intelligence (gen AI) is changing history and historical disciplines. Topics covered include the impact of gen AI on historical practice, its effects on archival research, the ethics of its use, strategies for combating biases, and inclusivity. The participants are Canadian scholars chosen based on their prior publications about AI and history. They represent a range of disciplines and career stages and work in both French and English.